Clinical analysis of pulmonary embolism in a child with Mycoplasma pneumoniae pneumonia - Su, Hai-yan (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2012)
OBJECTIVE: To explore the essential points for diagnosis of pulmonary embolism in children with mycoplasma pneumonia